PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN HOTSPOT WIFI.ID DI DENPASAR - Ndoen, Jeremy Roy Agutin; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2019)
T his study aims to clarify the role of customer satisfaction in mediating the effect of perceived value on customer loyalty.This research was conducted in Denpasar using a sample size of 110 people withmethod non-probability in the form of purposive i sampling. Data i analysis techniques used in this research is the analysis of the path (path analyis) and Sobel test. The results showed that perceived value have significant and positive effect on customer satisfaction, as well as on customer loyalty. Furthermore, customer satisfaction have positive and significant effect on customer loyalty. Besides customer satisfaction simultaneously mediates the effect of perceived value on customer loyalty. These results illustrate that the marketing environment is dynamic, so as to maintain customer loyalty company is expected to create value in accordance with what is expected (the perception of) the minds of the customers so that the resulting satisfaction.